Prison Work-Release Programs and Incarcerated Women's Labor Market Outcomes. (November 2019) - Jung, Haeil; LaLonde, Robert J.
This article examines whether the work-release program in Illinois prisons increases women's earnings and employment. Using a large matched adminis-trative database, we find that a longer time served in an Adult Transition Center (ATC) increases total earnings and the probability of being employed during the time in an ATC, for both ATC parolees and dropouts. Furthermore, ATC parolees and dropouts with a longer stay in an ATC had sizable increases in their earnings and employment rates after incarceration. However, the incompletion of the ATC terms by ATC dropouts seemed to carry stigma that reduces their post-incarceration earnings or employment rates.